SANGGIT WOVEN IN THE MURAL CLADDING OF THE MICE HALL BUILDING IN EAST NUSA TENGGARA - Anto, Andra Arie; Sunarmi, Suranmi (Lakar: Jurnal Arsitektur, 2024)
Sanggit weaving has a long history in Indonesian culture. The motifs contained in these weaves often contain deep symbolic and philosophical meanings, reflecting the social, religious and natural environmental aspects of the local community. Along with the development of time and technology, woven fabric is now not only used traditionally but also has experienced innovation in various forms, including its use as mural cladding on buildings. Sangit Weaving NTT in the form of a mural on a modern building has aesthetic value with the aim of maintaining local cultural values as an identity. This research examines Sanggit Weaving from East Nusa Tenggara (NTT). It interprets it into the design of mural cladding on modern buildings, with the aim of exploring the potential of Sanggit Weaving as a mural cladding material and its impact on the aesthetic value and cultural identity of modern buildings. This research uses a qualitative approach with analytical descriptive methods. Interviews with weaving experts who participate directly in the making of weaving. These results were used to develop a model that integrates Sanggit motifs in weaving mural cladding on buildings. The implementation of this model was tested through a pilot project and evaluated based on feedback from various stakeholders. Research findings show that the incorporation of woven motifs in modern murals not only beautifies buildings but also strengthens local cultural identity and increases awareness of local cultural preservation. This research contributes to the understanding of how local cultural sanggit can create relevant and meaningful works of art, as well as inspire future generations to appreciate and continue local cultural heritage.